Perceived Herding Behavior and Experienced Regret on Crypto Asset’s Investment Decisions by Millennials - Elyza Putri Rosmiwilujeng; Made Dudy Satyawan; Halil Paino (International Economic Conference of Business and Accounting, 2024)
The number of crypto asset enthusiasts continues to increase significantly over the past few years. Badan Pengawas Perdagangan Berjangka Komoditi (Bappebti) noted that crypto investors in Indonesia had reached 17.25 million people in April 2023. As the number of enthusiasts in crypto assets evolving, crypto assets have a very volatile and difficult to predict its price characteristics. This causes a lot of irrational investor’s behavior towards their decisions. Under these conditions, investor’s behavior can be influenced by psychological and emotional factors such as herding behavior and experienced regret. The purpose of this research is to determine the effect of herding behavior and experienced regret on the decision to invest in crypto assets by millennials. The research method uses a survey method with the research sample consisting of students and employees who are domiciled in urban areas of Surabaya and Sidoarjo. The analysis technique used in this study is multiple linear regression analysis using SPSS version 26 software. The results of the research show that herding behavior and experienced regret have a partial positive effect towards millennials’ investment decisions in crypto assets.